Assessment of kinesiophobia in patients with chronic low back pain - Овдій, Марія; Asanova, Азізе (Psychosomatic Medicine and General Practice, 2025)
Background. Low back pain is one of the most common problems of the musculoskeletal system, requiring a multidisciplinary approach to treatment. Chronic low back pain leads to disability, poor quality of life, anxiety and depression. Fear of movement or kinesiophobia is a psychological factor associated with impaired functioning in people with chronic low back pain and a negative prognosis for recovery. Objective. To evaluate kinesiophobia and its associated indicators in patients with chronic low back pain for further development of preventive and therapeutic strategies. Materials and methods. On the basis of the Rehabilitation Department of the University Clinic of the Bogomolets National Medical University, a questionnaire and examination of people with chronic nonspecific low back pain aged 18-60 years were conducted. The subjects underwent an assessment of socio-demographic, anthropometric indicators, an assessment of kinesiophobia using The Tampa Scale of Kinesiophobia (TSK-11), an assessment of stress level using the PSS-10 (Perceived Stress Scale), an assessment of the level of impairment using the Oswestry Disability Index (ODI). Results. The study involved 100 patients, including 62 women and 38 men, with an average age of 34.7±12.3 years. The average pain intensity of the subjects was 47.2±18.6 mm. According to the VAS, about 32% had neuropathic pain, 44% had nociceptive pain, and 24% had mixed pain. According to the TSK questionnaire, it was found that 48% of the subjects had kinesiophobia, with an average score of 30.9±11.7. In the group of subjects with kinesiophobia, there were significantly higher rates of age (<0.05), VAS pain intensity (<0.01), stress level (<0.01) and functional limitations (<0.01) compared to those without kinesiophobia. Conclusions. Among patients with chronic low back pain, kinesiophobia occurs in almost half of the subjects. Among this group of subjects, kinesiophobia is significantly associated with older age, higher VAS scores, neuropathic type of pain, distress and sleep disturbance, and higher rates of impaired functioning.